Direct Numerical Simulations of a Sheared Interface at Low Wind Speeds With Applications to Infrared Remote Sensing - Handler, Robert A.; Zhang, Qi (IEEE journal of selected topics in applied earth observations and remote sensing, 2013)
The fluid mechanics associated with the interface between two fluids, and in particular air and water, is of obvious importance in interpreting and determining surface signatures in the radar, infrared (IR), and visible wavelengths of the electromagnetic spectrum. These dynamics also play an important role in the determination of the interfacial flux of heat, mass, and momentum at the air-sea interface. Here we present results of direct numerical simulations (DNS) of an undeformed interface subject to a constant shear and constant outgoing heat flux at three Reynolds numbers. Particular attention is payed to the surface temperature field and its relation to the velocity and vorticity fields. The importance of these results to current problems in IR remote sensing is discussed.